(untitled) (Fiep Bulletin - online, 2014)
Contemporary society is experiencing a period of intense technological change in pace irreversible, and these changes invade privacy, including the human being in the virtual world often without even giving him the right to decide whether it wants to be inserted either in the opportunities that their personal information are registered in various types of database is the capture of your image in cameras commonly existing entries in public places and private, digital camera, cell phones, phone calls, filling out electronic forms, among others. Therefore, this article is a brief study of the meaning of privacy and intimacy, bringing their legal protection, in this Constitution and legislation infra basically having as main method to analyze the Brazilian doctrine, secondarily articles and reviews on the internet willing, with purpose of creating questions and awareness about the need for an education focused on the social value in order to respect the intimacy and privacy, especially in virtual space before a right positivised.